The factors that influence the sport sponsorship recognition to Telekom Malaysia / Nurulhazwani Mohd Joaini - Mohd Joaini, Nurulhazwani (2011)
As TM’s sport sponsorship huge growingly, people now are familiar with the sponsorship done by TM. For instance is Liga Malaysia. Thus it has questioned about what factor is actually has influenced the recognition of sponsor. TM has continuously become one of the important sport sponsors in Malaysia. Currently, TM has signed the five years deal sponsorship with the Manchester United. They have struggled very much in becoming the sponsor as they believe that sponsorship is one of the medium to promote their product and introduced their brand names at the international level. The purpose of this study is to examine what factor has contribute to the recognition of sport sponsorship done by TM and the second purposes of this study is which sponsorship does influenced most to the recognition of sport sponsorship by TM. All the objective have been achieved thus the result of the study can be used as one of the important factor that can be considerate at the end of the year by allocating the 2012 budget. This study examines several factors that influence the recognition of the sponsorship done by the Telekom Malaysia. This independent variable had done by the previous researcher who was also done for the same purpose. A set of Questionnaire has been distributed to the respondent in order to measure the factors that influence the recognition. The result can be used to be considered in allocating the budget next year.